Floyd-Warshall Algorithm for Web-Based Route Optimization for a Road Network Study in Medan City - Faridawaty Marpaung; Arnita; Tommy; Putri Harliana (PT FORMOSA CENDEKIA GLOBAL, 2023)
The socio-demographic conditions of the region have an influence on the transportation performance in the region. This study aims to determine the shortest path between two specified points, namely the starting and the end point of several sub-districts in Medan city, especially the sub-district of Medan Amplas. To get the output, several steps are needed, namely collecting the coordinates of street names and road lengths, which is obtained from Google maps. Graphs are used to present the data. Data analysis is used by Floyd–Warshall Algorithm with HTML Web Application supported by PHP programming language, JavaScript and MySQL database. The test results using the Black Box method show that the system functionality is 100% running well. For testing, the results of the final W_ij and Z^* final matrix calculations generated by the system is same with the manual calculations. Finally, to test the reliability of the system made, the results of the reliability test show the truth of working well and it can be accepted. There are no path deviations, so that the results are as expected